Chronic and Acute Manipulation of Cortical Glutamate Transmission Induces Structural and Synaptic Changes in Co-cultured Striatal Neurons - Kuhlmann, Naila; Wagner Valladolid, Miriam; Quesada-Ramírez, Lucía; Farrer, Matthew J.; Milnerwood, Austen J. (Frontiers in Cellular Neuroscience, 2021)
In contrast to the prenatal topographic development of sensory cortices, striatal circuit organization is slow and requires the functional maturation of cortical and thalamic excitatory inputs throughout the first postnatal month. While mechanisms regulating synapse development and plasticity are quite well described at excitatory synapses of glutamatergic neurons in the neocortex, comparatively little is known of how this translates to glutamate synapses onto GABAergic neurons in the striatum. Here we investigate excitatory striatal synapse plasticity in an in vitro system, where glutamate can be studied in isolation from dopamine and other neuromodulators. We examined pre- and post-synaptic structural and functional plasticity in GABAergic striatal spiny projection neurons (SPNs), co-cultured with glutamatergic cortical neurons. After synapse formation, medium-term (24h) TTX silencing increased the density of filopodia, and modestly decreased dendritic spine density, when assayed at 21 days in vitro. Spine reductions appeared to require residual spontaneous activation of ionotropic glutamate receptors. Conversely, chronic (14 days) TTX silencing markedly reduced spine density without any observed increase in filopodia density. Time-dependent, biphasic changes to the presynaptic marker Synapsin-1 were also observed, independent of residual spontaneous activity. Acute silencing (3h) had no effect on presynaptic markers or postsynaptic structures. To induce rapid, activity-dependent plasticity in striatal neurons, a chemical NMDA receptor-dependent ‘long-term potentiation’ paradigm was employed. Within 30 minutes, this increased spine and GluA1 cluster densities, and the percentage of spines containing GluA1 clusters, without altering presynaptic signal. The results demonstrate that growth and pruning of dendritic protrusions is an active process, requiring glutamate receptor activity in striatal projection neurons. Furthermore, NMDA receptor activation is sufficient to drive glutamatergic structural plasticity in SPNs, in the absence of dopamine or other neuromodulators.